2003
DOI: 10.1002/chin.200335077
|View full text |Cite
|
Sign up to set email alerts
|

Novel Highly Regioselective VO(acac)2/TBHP Mediated Oxidation of o‐Alkenyl Phenols to o‐Hydroxybenzyl Ketones.

Abstract: KetonesKetones Q 0350 Novel Highly Regioselective VO(acac) 2 /TBHP Mediated Oxidation of o-Alkenyl Phenols to o-Hydroxybenzyl Ketones. -In addition to the title reaction of phenols (I) yielding ketones (II), a one-pot conversion of these phenols to benzofurans (V) is reported involving the oxidation and subsequent treatment with TFA. In the case of phenols (III), epoxides (IV) are isolated from the oxidation reaction. Probably, steric factors prevent further rearrangement of the epoxides to the desired ketones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…2‐((3,3‐Dimethyloxiran‐2‐yl)methyl)phenol 8 is a known compound (23). 1 H NMR (400 MHz, C 6 D 6 ): δ 7.08–7.06 (2H, m), 7.01–6.96 (2H, m), 2.87 (1H, d, J = 8 Hz), 2.84 (1H, d, J = 8.0 Hz), 2.74 (1H, t, J = 8.0 Hz), 1.55 (3H, s), 1.52 (3H, s).…”
Section: Methodsmentioning
confidence: 99%
“…2‐((3,3‐Dimethyloxiran‐2‐yl)methyl)phenol 8 is a known compound (23). 1 H NMR (400 MHz, C 6 D 6 ): δ 7.08–7.06 (2H, m), 7.01–6.96 (2H, m), 2.87 (1H, d, J = 8 Hz), 2.84 (1H, d, J = 8.0 Hz), 2.74 (1H, t, J = 8.0 Hz), 1.55 (3H, s), 1.52 (3H, s).…”
Section: Methodsmentioning
confidence: 99%
“…During their study, it was observed that the addition of acetic acid or BF 3 • Et 2 O resulted in the formation of benzofuran (Scheme 1c). 20 Later, Liu et al reported dehydrogenative oxygenation of C(sp2)−H bonds of ortho-alkenyl phenols with intramolecular phenolic hydroxy groups to access diverse benzofurans (Scheme 1c). 21 Looking at this background, we realized that there is no report on cycloetherification of the C(sp 2 )−H bond of phenols/naphthols having cyclic olefin on the ortho position.…”
Section: ■ Introductionmentioning
confidence: 99%